Advances in Antiviral Therapies Targeting Toll-like Receptors. (2nd April 2016) - Shah, Masaud; Anwar, Muhammad Ayaz; Kim, Jae-Ho; Choi, Sangdun
ABSTRACT: Introduction : Organisms have evolved a rapid and non-specific way to defend themselves via Toll-like receptors (TLRs), which recognize specific signatures present on invading microbes and viruses. Once detected, these receptors flood the cell with cytokines and IFNs that not only help to eradicate the invading viruses but also activate the adaptive immune response. Owing to difficulties in viral detection, a whole class of TLRs is dedicated to sensing viral nucleic acids, while other TLRs detect viral coat proteins and aid in establishing antiviral immunity. To protect humans better, TLRs and their downstream mediators can be used as potential drug targets, which can be either activated or inhibited, to counter viral infections. Areas covered : The current review focuses on TLR-targeting investigational drugs developed to treat viral diseases and virus-induced complications. Expert opinion : TLRs are a good choice for eradicating viral infections because they can fine-tune the immune response. However, TLRs should be exploited carefully, as there have been instances where their activation has led to unwanted responses in terms of both immune and viral activation. Therefore, more focus should be placed on novel drugs that can induce significant and long-term immunity, while concomitantly alleviating side effects.